2016
DOI: 10.3892/ol.2016.4660
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation reduces the expression of PNPLA7 in hepatocellular carcinoma

Abstract: Abstract. Liver cancer has a high morbidity and mortality rate, and is one of the most common types of cancer in men. PNPLA7 is a member of the patatin-like phospholipase domain-containing protein family which is involved in triglyceride hydrolysis, energy metabolism and lipid droplet metabolism. The liver is the most important energy metabolism organ; whether PNPLA7 is deregulated in liver cancer has not been previously reported. In the present study, reverse transcription-quantitative polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…A previous study by Zhang et al also reported the down‐regulation of PNPLA7 levels in both hepatocellular carcinoma (HCC) cell lines and tissues. ( 37 ) In addition, the clinical data available in this current study are single‐point measurements. Patients with high PNPLA7 are diagnosed as less severe; thus, PNPLA7 expression may serve as a good prognostic marker for fatty liver, such that only patients with lower PNPLA7 expression progress just like HCC.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Zhang et al also reported the down‐regulation of PNPLA7 levels in both hepatocellular carcinoma (HCC) cell lines and tissues. ( 37 ) In addition, the clinical data available in this current study are single‐point measurements. Patients with high PNPLA7 are diagnosed as less severe; thus, PNPLA7 expression may serve as a good prognostic marker for fatty liver, such that only patients with lower PNPLA7 expression progress just like HCC.…”
Section: Discussionmentioning
confidence: 99%
“…PNPLA7 (also known as NTE-R1 or NRE ) is a member of the PNPLAs family, and its encoded protein is very conservative in mice, rats and human. PNPLA7 plays an important role in the hydrolysis of triglycerides, energy metabolism, lipid formation and adipocyte differentiation [ 20 ]. Up-regulation of PNPLA7 indicates elevated blood lipids, which has some correlation with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…LPA is upregulated with adipocyte differentiation and obesity 46 and, therefore, it does not come as a surprise that PNPLA7 would be then less expressed in samples from obese pregnancies. In addition, it has also been reported that DNA methylation regulates PNPLA7 expression - it is down-regulated in hepatocellular carcinoma cell lines and tissue samples, via the mechanism of transcriptional silencing by promoter hypermethylation 47 .…”
Section: Discussionmentioning
confidence: 99%